THE COMBINATION INFUSION OF Talinum paniculatum (Jacq.) Gaertn., Centella asiatica (L.) Urb. AND Curcuma xanthorrhiza Roxb. EFFECTS ON TESTOSTERONE LEVELS AND INTRODUCTION, CLIMBING AND COITUS FREQUENCIES IN MALE SPRAGUE-DAWLEY RATS - Nuning Rahmawati; Ika Yanti Marfuatush Sholikhah (Jurnal Tumbuhan Obat Indonesia, 2019)
ABSTRACT Talinum paniculatum (som Java) reported to have many pharmacological activities such as increasing spermatozoa quality, cell regenerations, fertility, and antibacterial effect both empirically and scientifically. This study aimed to prove the combination infusion effects of som Java, gotu kola, and temulawak on introduction, climbing, and coitus levels as well as testosterone levels in male Sprague Dawley (SD) rats. SD rats were divided into 2 groups, control group received aquadest, treatment group received formula a mixture of som java Talinum paniculatum) root, gotu kola (Centella asiatica) herb, and Javanese turmeric (Curcuma xanthorrhiza) rhizome with the dose of 491,2 mg/200 g BW for 7 consecutive days. Artificial estrus of female SD rats were induced by administering estradiol valerat 2 mg/200 g BW 48 hours before observation. The determined parameters were levels of testosterone as well as introduction, climbing and coitus frequencies. Administration of estradiol valerat led to artificial estrus induction of female SD rats. The administration of the combination infusion dose 491.2 mg/200 g BW significantly increased testosterone level as well as introduction and climbing frequencies of male SD rats as of 27.77%; 86.39% and 69.17% respectively. ABSTRAK Som jawa (Talinum paniculatum) secara empiris dan ilmiah terbukti telah banyak dimanfaatkan oleh masyarakat untuk mengatasi berbagai masalah kesehatan diantaranya untuk meningkatkan kualitas dan kuantitas spermatozoa, regenerasi sel, fertilitas, dan sebagai antibakteri. Penelitian ini dilakukan untuk membuktikan efek peningkatan kadar hormon testosteron serta frekuensi introduction, climbing, dan coitus tikus jantan SD dari pengaruh infusa kombinasi som jawa, pegagan, dan temulawak. Hewan uji tikus galur SD dibagi menjadi 2 kelompok, yaitu kelompok kontrol diberikan akuades, sedangkan kelompok perlakuan diberikan infusa ramuan akar som jawa, herba pegagan, dan rimpang temulawak dosis 491,2 mg/200 g bb selama 7 hari berturut-turut. Induksi estrus artifisial tikus betina dengan pemberian estradiol valerat 2 mg/200 g bb dilakukan 48 jam sebelum pengamatan. Parameter yang diukur meliputi kadar testosterone, frekuensi introduction, climbing, dan coitus. Dibandingkan dengan kelompok kontrol, pemberian infusa ramuan tidak berefek pada frekunsi coitus, namun mampu meningkatkan kadar testosteron serta frekuensi introduction dan climbing tikus jantan sebesar 27,77; 86,39 dan 69,17%.